Self-report to investigate metacognition growth in writing - Dina Ramadhanti; Diyan Permata Yanda (Politeknik Negeri Bali, 2023)
This study aims to describe the validity and reliability of the Metacognition Growth Questionnaire in writing. Using a quantitative approach, measurements were made of the metacognitive growth questionnaire, which was developed based on the metacognitive process theory, which consists of three, parts: the process of raising awareness, the process of monitoring/evaluating, and the process of controlling/regulating. A total of 30 students were randomly selected to be used as test subjects for the questionnaire instrument. The validity of the questionnaire items is known by using the bivariate product-moment correlation test. The reliability of the questionnaire is known by using Alpha Cronbach. The results showed that as many as 40 questionnaire items were declared valid, and overall, the questionnaire items were declared reliable. Thus, as many as 40 questionnaire items can be used to measure of students' metacognition growth in writing.